A Methodological approach to quantifying plyometric intensity - Jarvis, M. M.; Graham-Smith, P.; Comfort, P. (The Journal of Strength and Conditioning Research, 2016)
In contrast to other methods of training, the quantification of plyometric exercise intensity is poorly defined. The purpose of this study was to evaluate the suitability of a range of neuromuscular and mechanical variables to describe the intensity of plyometric exercises. Seven male recreationally active subjects performed a series of 7 plyometric exercises. Neuromuscular activity was measured using surface electromyography (SEMG) at vastus lateralis (VL) and biceps femoris (BF). Surface electromyography data were divided into concentric (CON) and eccentric (ECC) phases of movement. Mechanical output was measured by ground reaction forces and processed to provide peak impact ground reaction force (PF), peak eccentric power (PEP), and impulse (IMP). Statistical analysis was conducted to assess the reliability intraclass correlation coefficient and sensitivity smallest detectable difference of all variables. Mean values of SEMG demonstrate high reliability (r = 0.82), excluding ECC VL during a 40-cm drop jump (r = 0.74). PF, PEP, and IMP demonstrated high reliability (r = 0.85). Statistical power for force variables was excellent (power = 1.0), and good for SEMG (power =0.86) excluding CON BF (power = 0.57). There was no significant difference (p > 0.05) in CON SEMG between exercises. Eccentric phase SEMG only distinguished between exercises involving a landing and those that did not (percentage of maximal voluntary isometric contraction [%MVIC] = no landing -65 ± 5, landing -140 ± 8). Peak eccentric power, PF, and IMP all distinguished between exercises. In conclusion, CON neuromuscular activity does not appear to vary when intent is maximal, whereas ECC activity is dependent on the presence of a landing. Force characteristics provide a reliable and sensitive measure enabling precise description of intensity in plyometric exercises. The present findings provide coaches and scientists with an insightful and precise method of measuring intensity in plyometrics, which will allow for greater control of programming variables.